Intensity Indicators of Bacterial Translocation in Experimental Acute Obstruction of Small and Large Intestine - D. K., Razikova (Journal of Innovation in Education and Social Research, 2024)
The bacterial translocation (BT) is the passage of bacteria through the mucous membrane of the gastrointestinal tract in extraintestinal body parts [8]. The "BT phenomenon" occurs quite frequently [1, 5, 9]. At present time, this phenomenon is interpreted in two ways: first supporters believe that BT is developing under the influence of stress, injury, or other external extreme impacts and reducing the activity of the immune system, with a pathogenetic link of some diseases; proponents of a second believe that BT is not only the transfer of pathogens endogenous infections in the internal environment of the organism, but also is a natural defense mechanism of the body [4, 6, 10].